Six-Year Experience of a Nurse-Led Colorectal Cancer Follow-Up Clinic. (20th May 2014) - Al Chalabi, Hasan; O'Riordan, James M.; Richardson, Alex; Flannery, Delia; O'Connor, Katrina; Stuart, Charlotte; Larkin, John; McCormick, Paul; Mehigan, Brian
Abstract : Aims and Objectives . To review the experience of a nurse-led colorectal cancer follow-up clinic in a tertiary referral colorectal cancer centre. Methodology . Data from the nurse-led colorectal cancer follow-up clinic in our unit was prospectively maintained in a colorectal cancer database. Data was analysed from January 1, 2006 until the December 31, 2011. Results . 1125 patients were diagnosed with colorectal cancer, and referred to our unit as a tertiary centre for specialised colorectal cancer. Nine hundred and four patients had surgical resection of their colorectal cancer. Four hundred and seven patients were referred to the nurse-led colorectal cancer clinic for surveillance. The mean age of the patient cohort was 67 years (range 32–88) and 56% of patients were male. One hundred and seventeen patients were discharged to their general practitioner having been disease free after 5 years of followup. Fifty-four patients were diagnosed with either local or distant recurrence. Conclusion . A nurse-led colorectal cancer follow-up clinic is running according to strict follow-up protocols. This type of clinic significantly reduces the number of routine follow-up patients that have to be seen by the colorectal surgical consultant.